Integrating Video Barcode Technology In Multimedia Spreadsheet Textbooks: A Modern Approach To Teaching Corporate Financial Statements - Saputra, Irwan Adimas Ganda; Pratiwi, Vivi; Andriansyah, Eka Hendi; Rohayati, Suci; Triani, Ni Nyoman Alit; Kurnia, Amanda Dwi; Saputro, Aldi; Nilasari, Aprillia (International Humanity Advance, Business & Sciences, 2025)
In education, digital transformation is accompanied by the need for new teaching media innovations to address the challenges of inadequate technical skills among accounting education students, particularly regarding the use of spreadsheets for financial statement preparation. This study aims to develop class multimedia textbooks in the form of spreadsheets integrated with QR Code videos and test their validity, practicality, and effectiveness in enhancing student understanding and skills. This utilizes a Research and Development (R&D) approach with the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The product was developed with text and visualization, supplemented by video tutorials accessed through QR Codes to enrich the learning experience. The textbooks were determined to have a very high level of purported validity through expert validation. Significant classroom implementation showed strong positive effects on student learning outcomes alongside positive perceptions toward ease of use and effectiveness. This research enriches the literature on the development of technological learning media in accounting education and demonstrates innovation in integrating print and digital media. Furthermore, this innovation supports the achievement of Sustainable Development Goal (SDG) 4, which aims for high-quality, inclusive, and adaptable education in the context of the 4th Industrial Revolution (IR 4.0).